2007
DOI: 10.1016/j.jpainsymman.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A National Guideline for Palliative Sedation in The Netherlands

Abstract: The first national guideline on palliative sedation in The Netherlands has been adopted by the General Board of the Royal Dutch Medical Association. By law, the physician is obliged to take this guideline into consideration. In this paper, we present the main principles of the guideline. Palliative sedation is defined as the intentional lowering of consciousness of a patient in the last phase of his or her life. The aim of palliative sedation is to relieve suffering, and lowering consciousness is a means to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
2
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 21 publications
1
87
2
8
Order By: Relevance
“…The authors identified inconsistencies and a lack of clarity on what constituted "intolerable" or "refractory" suffering and proposed that the patient's ability to consent should be explicitly recorded, that the team have a shared and explicit understanding of the terminology and definitions of sedation, and that formal mechanisms for support (such as clinical supervision) are offered to staff. The development of guidelines has become a focus and priority due to concerns and uncertainty surrounding decisionmaking dilemmas and the connotations and inferences related to euthanasia and palliative sedation (Abarshi et al, 2014;Schildmann & Schildmann, 2014;Cherny & Radbruch, 2009;Hauser & Walsh, 2009;Legemaate et al, 2007;Verkerk et al, 2007;de Graeff & Dean, 2007;Engström et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified inconsistencies and a lack of clarity on what constituted "intolerable" or "refractory" suffering and proposed that the patient's ability to consent should be explicitly recorded, that the team have a shared and explicit understanding of the terminology and definitions of sedation, and that formal mechanisms for support (such as clinical supervision) are offered to staff. The development of guidelines has become a focus and priority due to concerns and uncertainty surrounding decisionmaking dilemmas and the connotations and inferences related to euthanasia and palliative sedation (Abarshi et al, 2014;Schildmann & Schildmann, 2014;Cherny & Radbruch, 2009;Hauser & Walsh, 2009;Legemaate et al, 2007;Verkerk et al, 2007;de Graeff & Dean, 2007;Engström et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, the inability to report distress might also be 159 aggravated or even blocked by the use of drugs that might abolish 160 potential further communication and even facial expressions [9]. Palliative sedation is normal medical practice and must be clearly distinguished from the termination of life [35] Proportionality: the degree of sedation must not be deeper than necessary to relieve suffering [11,12,23,35] Palliative sedation will not (usually) hasten death (and that is certainly not the intention) [ [24] o ''Monitoring (observational) scales exist but the usefulness of these scales has not been proven'' [16] o ''Presently no particular scale can be recommended'' [16,24] ''Scales involving administration of painful stimuli are not acceptable'' [16] Frequency of monitoring: every 20 minutes until adequate sedation has been reached and then at least once a day [15,16] Nurses have the explicit task to observe, measure, and report [24] 161 Hence, some patients might have subjective phenomenological …”
mentioning
confidence: 99%
“…Algunos autores han propuesto que la descontinuación de la hidratación y nutrición serían un componente típico o esencial de la técnica de sedación en la etapa final de la vida (38)(39)(40)(41)(42). Es así como Rietjens, por ejemplo, introduce este aspecto en la misma definición de "sedación terminal", que para ese autor sería la administración de drogas para mantener al paciente en sedación profunda o coma hasta la muerte, sin darle nutrición o hidratación artificial(37:179).…”
Section: ¿Son Las Decisiones De Suspender Hidratación Y/o Nutrición Munclassified